Sustained censorship in MA (2026-02) (Morocco) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Morocco. Data sourced from OONI.
Censorship Incident ID: MA-2026-0219. Severity: critical. Confidence: 80%